De tegenstrijdigheden van Antonio Gramsci - Anderson, Perry; Zakowsky, Simon; Corijn, Eric; Corijn, Eric (Antwerpen Amsterdam : Leon Lesoil Internationale Socialistiese Publikaties, 1981)
Bibliotheek François Vercammen
Nederlands
Monografie
Keywords: Partito Communista Italiano (PCI).; Gramsci, Antonio